Does trait self-esteem serve as a resilience factor in maintaining affective well-being? Findings from daily diary studies in Singapore and the United States - NG, Matthew H. S. (Institutional Knowledge at Singapore Management University, 2022)
Research suggests that self-esteem could be a protective factor in stressful or unfavorable situations. However, little research has been done on the buffering role of self-esteem in the context of daily stressors on affective reactivity. Three daily diary studies (of which two were conducted in Singapore and one in the United States) were carried out to examine this relationship. In all three studies, trait self-esteem was measured at baseline. Subsequently, daily assessment was conducted on exposure to daily stressors, and positive and negative affect for seven to eight days. Multilevel modeling showed that trait self-esteem did not moderate the relationship between daily stressor exposure and daily affect. An internal meta-analysis aggregating the findings of all three studies was also consistent with our findings. These findings are contrary to previous literature surrounding the stress-buffering role of self-esteem.